Comparative study on degradation of propranolol and formation of oxidation products by UV/H2O2 and UV/persulfate (PDS). (1st February 2019) - Yang, Yi; Cao, Ying; Jiang, Jin; Lu, Xinglin; Ma, Jun; Pang, Suyan; Li, Juan; Liu, Yongze; Zhou, Yang; Guan, Chaoting
Abstract: The frequent detection of propranolol, a widely used β-blocker, in wastewater effluents and surface waters has raised serious concern, due to its adverse effects on organisms. UV/hydrogen peroxide (UV/H2 O2 ) and UV/persulfate (UV/PDS) processes are efficient in eliminating propranolol in various waters, but the formation of oxidation products in these processes, as well as the assessment of their toxicity, has not been systematically addressed. In this study, we identified and compared transformation products of propranolol produced by hydroxyl radical ( OH) and sulfate radical (SO4 - ). The electrostatic attraction enhances the reaction between SO4 - and the protonated form of propranolol, while OH shows non-selectivity toward both protonated and neutral propranolol species. The hydroxylation of propranolol by OH occurs at either amine moiety or naphthalene group while SO4 - favors the oxidation of the electron-rich naphthalene group. Further oxidation by OH and SO4 - results in ring-opening products. Bicarbonate and chloride exert no effect on propranolol degradation. The generation of CO3 - and Cl-containing radicals is favorable to oxidizing naphthalene group. The acute toxicity assay of Vibrio fischeri suggests that SO4 - generates more toxic products than OH, while CO3 - and Cl-containing radicals produce similar toxicity as SO4 - . High concentrations of bicarbonate in UV/H2 O2 increase the toxicity of treated solution. Graphical abstract: Image 1 Highlights: Propranolol degradation is comparatively studied in UV/H2 O2 and UV/PDS. CO3 . - and Cl-containing radicals react with propranolol . OH induces hydroxylation of propranolol at either amine or naphthalene group SO4 . -, CO3 - and Cl-containing radicals attack the naphthalene group SO4 . -, CO3 - and Cl-containing radicals generate more toxic products than OH